The benefit of rhythm-based interventions for individuals with autism spectrum disorder: a systematic review and meta-analysis with random controlled trials - Ding, Xiaofen; Wu, Jinlong; Li, Dong; Liu, Zexi (Frontiers in Psychiatry, 2024)
Individuals with autism spectrum disorder (ASD) exhibit impaired behavior synchronization, which is associated with social deficits. Numerous studies have demonstrated that rhythm-based interventions can effectively mitigate social deficits by promoting behavioral synchronization in individuals with ASD. Therefore, a review of the current literature is warranted in this field. The objectives of this review were to explore the effects of rhythm-based interventions on overall social skills and to study the differences in the effects of rhythm-based interventions on specific social skills.The databases PubMed, Web of Science, Scopus, and Psycinfo were systematically explored until March 2024. A total of eleven research studies, encompassing 408 participants diagnosed with ASD, were incorporated into the meta-analysis. Effect sizes (Hedges' g) were computed for each comparison and amalgamated using random-effects models to evaluate the social skills of individuals with ASD. The methodological quality of each study was evaluated using the Physiotherapy Evidence Database scale(PEDro ).Overall, some valuable observations were made. Rhythm-based interventions had a medium effect on the overall social skills for ASD (Hedges's=0.681; 95%CI[0.075 to 1.286], P < 0.05).Regarding domain-specific social skills, rhythm-based interventions had a large effect on social interaction (g = 1.299,95% CI [0.508 to 2.091]), a small effect on communication (g = 0.383, 95% CI [0.033 to 0.733], P < 0.05), and a a large effect on emotion (g = 1.752, 95% CI [0.294 to 3.210], P < 0.05). However, we found a favorable but non-significant effect (g = 0.125, 95% CI [-0.039 to 0.289], P > 0.05) of rhythm-based interventions on empathy. All study qualities were high (score≥6) using the Physiotherapy Evidence Database (PEDro) scale assessment.This result indicates the importance of rhythm in the clinical rehabilitation of individuals with ASD. We suggest adding appropriate rhythmic elements to clinical interventions, particularly for individuals with ASD who are less socially competent.